ANALISIS EKSPERIMENTAL TURBIN PELTON SEBAGAI PEMBANGKIT LISTRIK MIKRO HIDRO DENGAN VARIASI NOZZLE - Niti Sumita, Vito Cristianto; Darmawan, Steven; Rosehan (Program Studi Teknik Mesin Universitas Tarumanagara, 2023)
Microhydro Power Plant is a small-scale power plant that utilizes river water flow to drive turbines. Some hydropower systems can be classified as microhydro if the generated energy capacity is below 100 kW [4]. The goal to be achieved from this pelton turbine research with nozzle variations is to determine the effect of nozzle size on flow discharge, torque and turbine rotation speed on pelton turbines. Pelton turbine research for this laboratory scale was carried out at the Heat and Heat Transfer Laboratory. In the first test, the water discharge was 50 l/min which produced a shaft rotation of 102 rpm. The minimum power generated at a discharge of 50 l/min (0.00083m3/s) occurred at a shaft speed of 102 rpm of 11.7 watts. Turbine power is highly dependent on the amount of torque and angular velocity. While the angular velocity is influenced by the rotation of the turbine and the rotation of the turbine is very dependent on the mass of the flow that hits the turbine blades. In the first test, the turbine power was 11.7 watts which resulted in an efficiency of 8%.